COGNITIVE ADAPTATION OF A SUBJECT TO SITUATIONS OF CHANGE IN DIFFERENT SPHERES OF LIFE - Khokhlova, Yu.A.; Ekimchik, О.А. (Modern Psychology, 2019)
This article presents the results of a pilot study of cognitive adaptation of the subject to situations of life changes. In the pilot study, only some results are presented, the main idea of a large-scale study will be revealed later. The aim of this study is to study the situations of change and stress of change in different spheres of life. The aim of the main study is to study the process of cognitive adaptation of the subject to these changes. Special attention is paid to the role of cognitive distortions and irrational attitudes in the process of cognitive adaptation.
Keywords: life changes, stress of changes, cognitive adaptation, cognitive distortions, irrational beliefs.